PELAKSANAAN PEMBELAJARAN BERNYANYI SECARA UNISONO MENGGUNAKAN PENDEKATAN SAINTIFIK DI SMP NEGERI 22 PADANG - Nur Azimah; Jagar Lumbantoruan; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2018)
Abstract This article aimed to describe the implementation of singing learning on unisono by using a scientific approach in SMP Negeri 22 Padang. This research used descriptive qualitative method. The objects of this research were the art teacher of culture and students of class VII.2 which amounted to 30 students. Data collection was done by using literature study technique, observation, interview, and documentation. The results showed that the implementation of singing learning on unisono using scientific approach has not been done in accordance with the objective of the 2013 curriculum caused by several things: 1) the unbalanced between the cognitive, affective, and psychomotor aspects of the learning implementation plan designed by the teacher, 2) the implementation of learning not in accordance with the RPP and still the combination of the learning approach with the methods and learning strategies in the curriculum KTSP, 3) learning evaluation had not been seen in the learning process, the evaluation was only taken at the time of exercise or daily tasks, daily test, mid semester, and final examination, so students were less active, creative, and innovative in the learning process. Keywords: Singing Unisono, the Scientific Approach.